Marcas da Memória: a atuação da Comissão de Anistia no campo das políticas públicas de transição no Brasil - Roberta Camineiro Baggio (Ciências Sociais Unisinos)
This article aims to demonstrate the importance of the role of the state in the articulation of social agents committed to the realization of the pillars of transitional justice in Brazil by analyzing the project Marcas da Memória (Marks of Memory). The project is a public policy created by the Brazilian Amnesty Commission of the Ministry of Justicein order to promote cultural initiatives of civil society that have the goal of expanding the right to memory and truth.